(untitled) (New York, 2006)
The book places the needs of English language learners and students with disabilities front and center instead of treating them as special topics. Accessible chapters on each of the core components of literacy clearly demonstrate how to link formal and informal assessment to evidence-based instruction. Special features include Research Briefs, Tech Tips, Internet Resources, Reflection and Action Questions, and dozens of reproducible student activities and assessment tools.
Keywords: Arts,Creative ability in children,Nghệ thuật,Reading (Elementary),Reading (Elementary); Study and teaching ( Early childhood ),Học tập và nghiên cứu (thời thơ ấu); United States.,Đọc (Tiểu học),United States.,United States